Analyzing The Presence of Russia in the Eastern Mediterranean Sea - Daniel Bryan; Muhammad Farid (AEGIS : Journal of International Relations, 2022)
The Mediterranean Sea has an attraction for countries that want to control this area. Among them are the abundant energy resources (such as oil and natural gas), have international trade routes that connect Europe, Africa, and Asia, and offer beaches or ports that can be built and operate year-round. Therefore, a superpower country like Russia is interested in becoming one of the actors that dominate this region. Russian activity in this region has occurred since the era of the Russian empire (Tsardom). However, over time, Russia has ambitions to regain control of the area they previously controlled. The Mediterranean region, especially the Eastern Mediterranean, is a strategic area for Russia in carrying out its foreign policy interests where they want to secure natural resource reserves and international trade routes and look for ports that can operate for a full year. This research aims to analyze how Russia's foreign policy interests result in its presence in the Eastern Mediterranean Sea. Using qualitative research methods, this research will analyze Russia's presence in the East Mediterranean Sea. This research finds that Russia can demonstrate its presence in the Eastern Mediterranean region by using several political manoeuvres such as the annexation of Crimea, establishing relations with Turkey and Syria, and the use of energy politics in their foreign policy.